ASSESSING LOCAL GOVERNMENT PERFORMANCE TO MANAGE POVERTY ALLEVIATION PROGRAM BASED ON VALUE FOR MONEY APPROACH - Tommy Anggriawan (Natapraja, 2022)
Various kinds of poverty reduction programs and activities have been implemented with large budget funds, but it is still difficult to see a clear justification on poverty reduction as a consequence of the policies that have been carried out. In order to increase the synergy of poverty reduction programs and to stimulate the economy of poor families, this research aims to measure the performance of the government of Pasuruan Regency by using a value for money approach based on the performance budget of a program, which uses the economy, efficiency, and effectiveness ratio. This research uses a case study research with a qualitative approach. Findings of this study indicate that the average economic ratio of the overall achievement ratio is 82.4%, it is considered economical. Overall, the efficiency ratio of the Pasuruan Regency Government's performance has been efficient, which is 134.1%,. Meanwhile, the effectiveness ratio obtained an average result of 122.41% thus it can be classified the performance of the Pasuruan Regency Government as a whole is considered effective, however, the performance of the two programs from the Health and Fisheries sector is considered ineffective. It still need a depth follow up on those programs to get a better synergy, comprehensive strategy in eradicate poverty.